PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI PENGURUS ORGANISASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA ORGANISASI KEMAHASISWAAN DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Ian Gibran Oksyah; Baiq Anggun Hilendri Lestari (Politeknik Negeri Ambon, 2026)
Introduction: This study examines the determinants of fund management accountability within student organizations at the Faculty of Economics and Business, University of Mataram, with an emphasis on the roles of internal control systems and administrators' competence. In practice, student organizations frequently face accountability challenges, including incomplete financial documentation, weak procedural compliance, and limited managerial capacity. Prior empirical findings on these relationships remain inconsistent and highly context-dependent, particularly within semi-formal organizations in higher education. Accordingly, this research seeks to reassess whether internal control systems and managerial competence significantly enhance accountability in student organization fund management.Methods: This research adopts a quantitative associative approach. Primary data were collected through questionnaires distributed to 127 core administrators of student organizations for the 2024–2025 period. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 to test the proposed hypotheses.Results: The findings demonstrate that the internal control system has a positive and statistically significant effect on fund management accountability. Administrator competence also shows a positive and considerable influence, indicating that knowledge, skills, and professional attitudes substantially contribute to transparent, compliant, and reliable financial reporting. Together, the two variables explain a considerable proportion of the variation in accountability.Conclusion and suggestion: Strengthening internal control mechanisms and improving administrator competence are essential to enhancing financial accountability in student organizations. In practice, the results highlight the importance of standardized financial procedures, structured supervision, and continuous training to support accountable governance in higher education institutions. Keywords: Accountability, Internal Control System, Management Competence, PLS-SEM,, Student Organizations